Coffee ingestion enhances 1-mile running race performance - Clarke, N. D.; Richardson, D. L.; Thie, J.; Taylor, R. (International Journal of Sports Physiology and Performance, 2018)
Context: Caffeine, often in the form of coffee, is frequently used as a supplement by athletes in an attempt to facilitate improved performance during exercise. Purpose: To investigate the effectiveness of coffee ingestion as an ergogenic aid prior to a 1-mile (1609 m) race. Methods: In a double-blind, randomized, cross-over, and placebo-controlled design, 13 trained male runners completed a 1-mile race 60 minutes following the ingestion of 0.09 g/kg coffee (COF), 0.09 g·kg-1 decaffeinated coffee (DEC), or a placebo (PLA). All trials were dissolved in 300 mL of hot water. Results: The race completion time was 1.3% faster following the ingestion of COF (04:35.37 [00:10.51] min:s.ms) compared with DEC (04:39.14 [00:11.21] min:s.ms; P=.018; 95% confidence interval [CI], -0.11 to -0.01; d=0.32) and 1.9% faster compared with PLA (04:41.00 [00:09.57] min:s.ms; P=.006; 95% CI, -0.15 to -0.03; d=0.51). A large trial and time interaction for salivary caffeine concentration was observed (P<.001; 2 p =.69 p2=.69), with a very large increase (6.40 [1.57] µg/mL; 95% CI, 5.5-7.3; d=3.86) following the ingestion of COF. However, only a trivial difference between DEC and PLA was observed (P=.602; 95% CI, -0.09 to 0.03; d=0.17). Furthermore, only trivial differences were observed for blood glucose (P=.839; 2 p =.02 p2=.02 ) and lactate (P=.096; 2 p =.18 p2=.18) and maximal heart rate (P=.286; 2 p =.13 ?p2=.13) between trials. Conclusions: The results of this study show that 60 minutes after ingesting 0.09 g·kg-1 of caffeinated coffee, 1-mile race performance was enhanced by 1.9% and 1.3% compared with placebo and decaffeinated coffee, respectively, in trained male runners.